2014
DOI: 10.5123/s1679-49742014000200018
|View full text |Cite
|
Sign up to set email alerts
|

Toxocaríase, asma e índice de massa corporal em crianças e adolescentes em Campinas-SP, 1996 a 1998

Abstract: Objetivo: analisar a associação entre diagnóstico de asma e índice de massa corporal (IMC) em crianças e adolescentes com e sem marcador sorológico para toxocaríase. Métodos: estudo transversal, com dados dos prontuários de indivíduos de 2 a 14 anos de idade avaliados quanto à infecção por toxocaríase na unidade básica de saúde do Jardim Santa Mônica, Município de Campinas-SP, Brasil, tendo por referência o período de 1996 a 1998; para o estudo das associações entre presença de toxocaríase, asma e IMC, utilizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In 2012, Mendonça et al 51 did not find an association between positivity for aeroallergens and Toxocara infections in children living in poor areas of Salvador (Bahia State) and postulated that increased polyclonal IgE levels and the induction of a modified Th2 immune response to Toxocara infection might prevent the development of skin hypersensitivity to aeroallergens. On the other hand, Fialho and Corrêa 57 found an association between asthma and increased body mass index in children and adolescents living in Campinas (São Paulo State), and Fialho et al 58,59 confirmed a positive association between urticaria and infection with Toxocara in children.…”
Section: Frequency and Characteristics Of Human Infections Due To Toxocaramentioning
confidence: 97%
“…In 2012, Mendonça et al 51 did not find an association between positivity for aeroallergens and Toxocara infections in children living in poor areas of Salvador (Bahia State) and postulated that increased polyclonal IgE levels and the induction of a modified Th2 immune response to Toxocara infection might prevent the development of skin hypersensitivity to aeroallergens. On the other hand, Fialho and Corrêa 57 found an association between asthma and increased body mass index in children and adolescents living in Campinas (São Paulo State), and Fialho et al 58,59 confirmed a positive association between urticaria and infection with Toxocara in children.…”
Section: Frequency and Characteristics Of Human Infections Due To Toxocaramentioning
confidence: 97%
“…10,27,[30][31][32]36,40 In all of these studies, a higher proportion of patients with asthma was found among those infected with Toxocara, which lends this infection greater relevance in terms of public health.…”
Section: Resultsmentioning
confidence: 97%
“…10,[24][25][26][27][28][29][31][32][33][34][36][37][38][39][40][41][42][43][44] One study did not describe the diagnostic methodology applied. 35 As T. canis and T. cati cannot be distinguished serologically, we identified the study population as having toxocariasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation